Analisis Metode Kerja Perakitan Kipas Angin Pada Proses Servis Kipas Angin Menggunakan Peta Tangan Kiri dan Tangan Kanan - Galuh Krisna Dewanti (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
This research was conducted at the "ABC" electronics workshop. The problem that has been experienced by the "ABC" workshop is the process of servicing an tool is too long, one of which is the work of fan service. From the results of research conducted, why the servicing of an tool is too long because there is no standard workmanship in the service process (SOP), Laying spare parts / components that are not fixed, service equipment is mixed with goods that are not tools, layout spare parts and work tables that are too far away cause transportation (transfer of technicians) to take longer parts / tools. The method used in this research is to use the Left and Right Hand Maps. The purpose of this study is to propose improvements to work methods using maps of the right hand and left hand. The results of this study show there is a decrease in fan assembly time from 301 seconds to 276 seconds.